Predictive value of total immunoglobulin E (IgE) levels in some allergic diseases in children - الفاحلي, اسعد; فيصل رضوان ,; راما إبراهيم, (Latakia University Journal -Medical Sciences Series, 2023)
Background: Allergic diseases, whether respiratory, such as allergic asthma and allergic rhinitis, or skin diseases such as eczema, are among the common diseases in Syria. Therefore, understanding the markers is critical for the likelihood of early detection of these disorders. Objectives: To determine whether the serum concentrations of total immunoglobulin (IgE) are significant in early diagnosis of allergic diseases and thus its importance in predicting their occurrence, so we measured the serum levels of total immunoglobulin (IgE) in a group of pediatric patients who had allergic skin and respiratory symptoms. Methods: In our study, 75 children with respiratory or cutaneous allergies were included alongside 25 healthy children serving as a control group. We measured their total IgE levels using the FEIA method. Results: The mean total IgE levels in the group of children who developed an allergic disease after follow-up for one year [484.06 ± 175.76 IU/mL] were greater than the mean levels of total IgE levels in the group of children who did not develop an allergic disease after follow-up [212.50 ± 74.64 IU/mL], with a significant difference in favor of the group of patients who developed a disease after follow-up (P<0.001). IgE levels had a diagnostic sensitivity of 91.5%, diagnostic specificity of 87.5%, a positive predictive value of 96.4%, and a negative predictive value of 70% in pediatric patients, at a cut-off = 305 IU/ml. Conclusion: Total IgE levels have a high predictive value for allergic diseases in children.